Mengeksplorasi Pengaruh Pemberian Kompos Batang Pisang terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L.) di Media Podsolik Merah Kuning (PMK) - Elleanor Perada Payon, Mekhtildis; Sopiana, Sopiana; Nurhayati, Nurhayati (Politeknik Negeri Ketapang, 2024)
This study aims to explore the effect of banana stem compost on the growth of cocoa seedlings (Theobroma cacao L.) in PMK media. This study used a non-factorial completely randomized design (CRD) with 6 treatments and 4 replications so that there were 24 experimental units, each experimental unit consisted of 3 samples so that the total number of samples was 72. The treatments consisted of K0: Without banana stem compost, K1: Banana stem compost 300 g/polybag, K2: Banana stem compost 375 g/polybag, K3: Banana stem compost 450 g/polybag, K4: Banana stem compost 525 g/polybag K5: Banana stem compost 600 g/polybag. The data obtained were analyzed using Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) at the 5% level. Based on the analysis of variance, the application of banana stem compost in PMK media has a significant effect on seedling height, stem diameter, number of leaves, root length, and dry weight of cocoa seedlings. The best growth of cocoa seedlings in PMK media is by applying banana stem compost at a dose of 600 (g/polybag).